Dose and Schedule Selection of the Oral Proteasome Inhibitor Ixazomib in Relapsed/Refractory Multiple Myeloma: Clinical and Model-Based Analyses - Gupta, Neeraj; Yang, Huyuan; Hanley, Michael J; Zhang, Steven; Liu, Rachael; Kumar, Shaji; Richardson, Paul G; Skacel, Tomas; Venkatakrishnan, Karthik (Targeted oncology, 2017)
BACKGROUND: The oral proteasome inhibitor ixazomib has been approved by regulatory authorities around the world, including in the United States and the European Union, for the treatment of patients with multiple myeloma (MM) who have received at least one prior therapy, based on the pivotal phase III TOURMALINE-MM1 study. OBJECTIVE: The objective of this study was to quantitatively characterize the benefit-risk profile of ixazomib in relapsed/refractory MM in support of the approved dose and schedule. METHODS: We report early-phase study data and exposure-response analyses of TOURMALINE-MM1 data that support the selection of the recommended ixazomib dose and schedule. RESULTS: Single-agent ixazomib studies showed a favorable efficacy/safety profile with weekly versus twice-weekly dosing; a phase I/II study of ixazomib in combination with lenalidomide and dexamethasone (IRd) identified a weekly ixazomib dose that offered an acceptable efficacy/safety profile. In IRd exposure-response analyses from TOURMALINE-MM1, ixazomib systemic exposure was not a significant predictor of progression-free survival or probability of response. Significant associations were observed between ixazomib exposure and the probability of grade ≥3 anemia and thrombocytopenia, and grade ≥2 diarrhea, fatigue, nausea, peripheral neuropathy, and rash. Additionally, higher ixazomib exposure was associated with lower lenalidomide relative dose intensity. CONCLUSIONS: These analyses support a favorable benefit-risk profile for weekly ixazomib 4.0 mg on days 1, 8, and 15 of 28-day cycles, which was selected for the phase III TOURMALINE registration program. TRIAL REGISTRATION NUMBERS: ClinicalTrials.gov NCT00932698, NCT00963820, NCT01217957, NCT01564537.
Keywords: Proteasome Inhibitors; Disease-Free Survival; Male; protinádorové látky; lokální recidiva nádoru; inhibitory proteasomu; vztah mezi dávkou a účinkem léčiva; Multiple Myeloma; mužské pohlaví; Neoplasm Recurrence, Local; lidé; ženské pohlaví; glycin; Humans; Glycine; sloučeniny boru; Boron Compounds; mnohočetný myelom; Female; Dose-Response Relationship, Drug; přežití bez známek nemoci; Antineoplastic Agents